Representativeness Heuristic, Investment Decisions, and Financial Performance of Small and Medium Enterprises in Nairobi, Kenya - Koech, Alex; Koske, Naomi; Cheboi, Josphat (African Journal of Education,Science and Technology (AJEST), 2020)
Heuristic factors play an undeniable role in influencing individuals’ decisions, including investment decisions. They have emotional impact on all investors and vary subject to the investor’s nature which affects the financial performance of the firm. Investors have a specific way of intellectual and feeling which affects their actions when making investment decisions. These influences are called psychological or behavioral heuristics. Using cross-sectional data from 382 respondents of small and medium enterprises located in Nairobi County, the research evaluated the direct influence of Representativeness Heuristic on the financial performance of the SMEs in Nairobi County. In addition, the research scrutinized the mediational effect of Investment decisions on the relationship between Representativeness heuristic and the financial performance of the said SMEs. The study is guided by Heuristic theory and Modern portfolio theory. The study used an explanatory research design and arranged the samples into strata. Data collection was done through self-administered, structured questionnaires and elements were grounded on a 5-point Likert scale after which data analysis was done using descriptive and inferential statistics. The study hypotheses were tested with the use of multiple regression models and Hayes process macro. The results showed that Representativeness Heuristics significantly predicts SME’s financial performance (β= .169, p< .05) and this relationship is partially mediated by Investment decisions (β =.285, p < .001, CI=0.023, 0.099). Theoretically, the study supported the incorporation of different key dimensions of heuristic factors and investment decisions to achieve the financial performance of SMEs. Finally, there is a need to undertake similar studies covering other geographical locations to make a generalization of this study.